Student Perceptions of Science Subjects at State Vocational Schools in Central Lombok Regency - Azizi, Asrorul; Jufri, A. Wahab; Sarjan, M.; Ariansani, Yunita; Rokhmat, Joni; Sukarso, AA (Universitas Pendidikan Mandalika, 2023)
Vocational High School (SMK) is an education that prepares students to become professionals according to their program of expertise. In addition to learning science in vocational education subjects, which is something new, the previous vocational subject curriculum did not study science. The purpose of this study was to describe students' perceptions of science learning at State Vocational High School (SMKN) 1 Praya, SMKN 1 Pujut , and SMKN 1 West Praya. This research includes descriptive research. The sample in this study was 20% of the tenth grade students of Paiwisata Vocational High School in Central Lombok district, totaling 37 students SMKN 1 Praya, 25 students of SMKN 1 Pujut, and 26 students of SMKN 1 West Praya . Sampling was done by simple random sampling, and the instrument used for data collection was a questionnaire. The data analysis technique used is percentage. Students' Perceptions of Research Results in Science Lessons show a percentage of 74.02% with sufficient criteria. It can be concluded that students' perceptions of learning science meet sufficient criteria.